The Effect of Doctor Presence and Services on Patient Satisfaction Moderated in Collaboration at Citra Sari Husada Karawang Hospital - Tri Agus Haryono; Adrie Frans Assa (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study aims to find out and analyze the influence of the presence of doctors and services on patient satisfaction moderated by Cooperation at Citra Sari Husada Hospital Doctors or health workers and hospitals as health facilities are unsure providers who will provide health services to the receiver which in this case is the patient. The research method used is Quantitative with SmartPLS 3 data analysis with a total of 100 respondents at Citra Sari Husada Hospital. Service to Patient Satisfaction, has an effect with a coefficient of 0.265 and a t-statistic of 1.702. Cooperation on Patient Satisfaction has an effect with a coefficient of 0.408 and a t-statistic of 1.792. Meanwhile, Service has an influence on Cooperation with a coefficient of 0.532 and a t-statistic of 6.231. Not all associations were significant at the level of 0.05 (p < 0.05), which confirms not all research hypotheses are significant.